2012
DOI: 10.1177/1049732312443737
|View full text |Cite
|
Sign up to set email alerts
|

Using First Nations Children’s Perceptions of Food and Activity to Inform an Obesity Prevention Strategy

Abstract: Obesity and associated health risks disproportionately affect Aboriginal (First Nations) children in Canada. The purpose of this research study was to elicit First Nations children’s perceptions of food, activity, and health to inform a community-based obesity prevention strategy. Fifteen 4th- and 5th-Grade students participated in one of three focus group interviews that utilized drawing and pile-sorting activities. We used an ecological lens to structure our findings. Analyses revealed that a variety of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 32 publications
(48 reference statements)
0
35
0
Order By: Relevance
“…Engaging with family was an important aspect of eating traditional food. Recently, Pigford et al (2012) also found that Aboriginal children's experiences around traditional food involved nuclear and extended family. Thompson, Gifford, and Thorpe (2000) suggests that for Aboriginal People, family is central to every aspect of food, including choice, preparation, and what it represents.…”
Section: > > Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Engaging with family was an important aspect of eating traditional food. Recently, Pigford et al (2012) also found that Aboriginal children's experiences around traditional food involved nuclear and extended family. Thompson, Gifford, and Thorpe (2000) suggests that for Aboriginal People, family is central to every aspect of food, including choice, preparation, and what it represents.…”
Section: > > Discussionmentioning
confidence: 99%
“…Past research has shown that culture is a determinant of Aboriginal Peoples' diets, including Aboriginal children living in rural or on-reserve First Nations communities (Pigford, Willows, Hold, Newton, & Ball, 2012;Willows, 2005). Aboriginal youth's lives are often a blend of both modern and traditional lifestyles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Younger community members often report a preference for store-bought foods (Bruner & Chad, 2013), as was also mentioned by participants with young children in this study, along with women who did not have the same familial connections with these foods. Research in rural and urban Alberta is, however, demonstrating that family and school can positively influence traditional food experiences (Kerpan et al, 2015;Pigford, Willows, Holt, Newton, & Ball, 2012). Increased exposure to these foods through school programs, cultural activities, and family events has been shown to increase both the frequency of consumption and taste preferences among urban youth.…”
Section: Discussionmentioning
confidence: 99%
“…Increased exposure to these foods through school programs, cultural activities, and family events has been shown to increase both the frequency of consumption and taste preferences among urban youth. On reserves, knowledge gained from Elders and family members most consistently informed children's food preferences and health beliefs (Pigford et al, 2012).…”
Section: Discussionmentioning
confidence: 99%